UJI AKTIVITAS ANTIOKSIDAN DAN TOTAL FLAVONOID PADA EKTRAK ETANOL PINANG YAKI (Areca vestiaria) - Samosir, Ary Pratama; Runtuwene, Max Revolta John; Citraningtyas, Gayatri (PHARMACON, 2012)
This study aims to determine the antioxidant activity of the ethanol extract in fresh Pinang Yaki (Areca vestiaria) seeds and the total content of flavonoid compounds. Total Antioxidant test used Ferric Reducing Antioxidant Power (FRAP) method and Chang method, 2002, for calculate the total flavonoids and for test the antioxidant activity. Result from this study showed that the antioxidant activity of fresh samples is 3.80375 mmol/100g and the total flavonoids in fresh samples is 7.2374 mg / kg. Keywords : fresh samples of Pinang Yaki (Areca vestiaria), Antioxidant, total flavonoids, Ferric Reducing Antioxidant Power (FRAP)